Resource Allocation Algorithms Supporting Coexistence of Cognitive Vehicular and IEEE 802.22 Networks - You Han; Ekici, Eylem; Kremo, Haris; Altintas, Onur (IEEE transactions on wireless communications, 2017)
Many studies show that the dedicated short range communication (DSRC) band is insufficient to carry increasing wireless traffic demands in vehicular networks. The release of TV white space band by the Federal Communications Commission (FCC) for cognitive access provides additional bandwidth to solve the DSRC spectrum scarcity problem. However, FCC requires portable devices to use significantly lower transmitting power than fixed devices, which creates a challenging coexistence environment for portable (e.g., vehicular) and fixed (e.g., IEEE 802.22) networks. In this paper, we address the coexistence problem between a vehicular and an 802.22 network via resource allocation. We first formulate the coexistence problem as a mixed-integer nonlinear programming (MINLP) problem, to which three algorithms are developed. The first algorithm converts the MINLP into a convex program and obtains a near-optimal solution to the initial MINLP. In the other two algorithms, we first convert the MINLP into an integer programming (IP) problem. Then, we solve the linear program relaxation of the IP and obtain a fractional solution. Thereafter, two rounding algorithms are developed to round the fractional solution based on column-sparse packing and dependent rounding techniques, respectively. Finally, we compare the performance of the proposed algorithms with an optimal MINLP solver through numerical examples.